MODEL OF CAUSALITY BETWEEN FOREIGN DIRECT INVESTMENT AND GROSS DOMESTIC PRODUCT ON ASEAN-5 COUNTRIES FROM 1980-2014 - Supriyadi, Dedy; Satria, Dias (Journal of Indonesian Applied Economics, 2017)
The study examines the relationship between foreign direct investment (FDI) and gross domestic product (GDP) for ASEAN-5 countries between periods 1980 to 2014. The study uses a Toda-Yamamoto granger causality model to test the causality between the FDI and the GDP. The results show that the ASEAN countries are differently in responding the impacts of FDI to the GDP.Â